Differences in Reading Strategies: How esl Learners Really Read - Noli Maishara, Nordin; Sabariah, Md. Rashid; Sharifah Intan Safina, Syed Zubir; Roslan, Sadjirin (Elsevier, 2013)
Students’ comprehension of a text relies much on the use of appropriate reading strategies during the activity. The use of such strategies would improve students’ comprehension of the text, which, in turn helps them in their academic achievement at large. This study aimed to investigate the reading strategies used by ESL learners at tertiary level. Specifically, it aimed to identify the reading strategies frequently used by the ESL high and low achievers. It also aimed to find out whether there was any significant different in the type of strategies used by each group of ESL achievers. Forty undergraduate students were randomly selected as the respondents for this study. A twenty-eight-item questionnaire, which focused on the frequency of use of pre, while, and post-reading strategies was utilised in the study. It was found that both of the ESL high and low achievers frequently used certain reading strategies to grasp the meaning of the text. The ESL high achievers were also reported to significantly use post-reading strategies more frequently as compared to the ESL low achievers who tended to use while- reading strategies more frequently. The findings suggest that the use of appropriate reading strategies should be exposed to students to help them enhance their comprehension of a reading text and make them become better readers.